Preterm premature rupture of membranes: Which criteria contraindicate home care management?. (6th September 2018) - Petit, Céline; Deruelle, Philippe; Behal, Hélène; Rakza, Thameur; Balagny, Sara; Subtil, Damien; Clouqueur, Elodie; Garabedian, Charles
Abstract: Introduction: Home care management offers a suitable alternative to hospitalization for management of preterm premature rupture of membranes (PPROM). Eligibility criteria have not been clearly established. Our aim was to determine predictive factors of complication during home care management of PPROM in order to define optimal eligibility criteria. Material and methods: Retrospective cohort study of all women with singleton pregnancies with PPROM managed as outpatients between 2009 and 2015. Complications were defined as the occurrence of one of these events: fetal death, placental abruption, umbilical cord prolapse, delivery outside maternity hospital, neonatal death. Results: In all, 187 women with PPROMs were managed as outpatients, of whom 12 had a complication (6.4%). In the "complication" group, gestational age at diagnosis ( P  = 0.006) and at delivery ( P  < 0.001) were lower, with no difference in latency between these two events. Three criteria significantly increased the risk for a severe complication: PPROM occurring before 26 weeks ( P  = 0.008), non‐cephalic fetal presentation ( P  = 0.02) and oligoamnios ( P  = 0.02). When unfavorable criteria were associated with PPROM, the risk was increased (1 criterion, odds ratio [OR] 1.6; 2 criteria, OR 6.9 and 3 criteria, OR 32.8). Conclusions: Combination of these three criteria is an indication for conventional hospitalization to limit maternal and fetal morbidity. When two criteria are combined, home care should be discussed for each case. If only one unfavorable criteria is present, outpatient management is suitable. To validate these results, a prospective randomized study should be conducted.